2007
DOI: 10.1186/1471-2164-8-212
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a candidate gene (MdMYB10) for red flesh and foliage colour in apple

Abstract: Background: Integrating plant genomics and classical breeding is a challenge for both plant breeders and molecular biologists. Marker-assisted selection (MAS) is a tool that can be used to accelerate the development of novel apple varieties such as cultivars that have fruit with anthocyanin through to the core. In addition, determining the inheritance of novel alleles, such as the one responsible for red flesh, adds to our understanding of allelic variation. Our goal was to map candidate anthocyanin biosynthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(124 citation statements)
references
References 49 publications
3
119
0
2
Order By: Relevance
“…This marker co-segregates with the Rni locus, which is positioned on LG 09, a region that has been previously implicated in the control of red skin color. Previous research has suggested that Rf and Rni might be located in a gene cluster, or even correspond to alleles of the same gene, because they are both located at the bottom of LG 09 on the apple genome (Maliepaard et al, 1998;Chagné et al, 2007). Moreover, in our study, the evaluation of 30 cultivars and two progenies produced consistent results for the 2 DNA markers ( Table 2, Table 4).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This marker co-segregates with the Rni locus, which is positioned on LG 09, a region that has been previously implicated in the control of red skin color. Previous research has suggested that Rf and Rni might be located in a gene cluster, or even correspond to alleles of the same gene, because they are both located at the bottom of LG 09 on the apple genome (Maliepaard et al, 1998;Chagné et al, 2007). Moreover, in our study, the evaluation of 30 cultivars and two progenies produced consistent results for the 2 DNA markers ( Table 2, Table 4).…”
Section: Discussionsupporting
confidence: 83%
“…In apple, 2 other genes (MdMYB10 and MdMYBA), which are homologous to MdMYB1, have been isolated, and shown to regulate anthocyanin biosynthesis in apple skin or flesh (Takos et al, 2006;Ban et al, 2007;Espley et al, 2007). Chagné et al (2007) derived a molecular marker (NZms_MdMYB10) from MdMYB10, which is able to control red color in apple. This marker co-segregates with the Rni locus, which is positioned on LG 09, a region that has been previously implicated in the control of red skin color.…”
Section: Discussionmentioning
confidence: 99%
“…Only the QTL cluster on LG 9 (both parents) and on the cv Telamon LG 16 were specific for skin AsA concentrations. These regions on LG 9 and LG 16 have both been shown to contain major QTL for apple fruit polyphenolic contents (Chagné et al, 2007(Chagné et al, , 2012Khan et al, 2012). We have previously reported that the sunexposed (red) side of apples has higher anthocyanin and AsA concentrations and is more resistant to both biotic and abiotic stress than the shaded (green/ yellow) side (Davey et al, , 2007, and recently, Bulley et al (2012) demonstrated that transgenic fruits from tomato and strawberry with elevated AsA contents also had an approximately 50% larger polyphenolic pool.…”
Section: Discussion Antioxidant Concentrations and Qtl In The CV Txbmentioning
confidence: 98%
“…Red-fleshed apples are not widely produced because of poor fruit quality (e.g., linkage group (LG) 9 (Chagné et al, 2007;Volz et al, 2013), and the other, MdMYB110a, is located on LG 17 Umemura et al, 2013). In apples with MdMYB10, designated as type 1, not only the flesh, but also other organs including the skin, flower, leaf, and stem, are red in color.…”
Section: Introductionmentioning
confidence: 99%